Globalization processes in Baltic countries: Analysis of trends in Lithuania, Latvia and Estonia - Ginevičius, Romualdas; Tvaronavičienė, Manuela (Journal of Business Economics and Management, 2003)
The paper scrutinizes issues concerning factors determining inflow of foreign direct investments into Baltic States. It aims to determine what drives foreign capital to considered region, and if different approaches to conditioning business environment matter.First Published Online: 14 Oct 2010